Female genital tuberculosis presenting as a protruding anterior vaginal wall mass: a case report - Mequanint Melesse Bicha; Tewodros Zenabu Kebede; Ayalew Lingerih Arefeaynie; Eden Woldegerima Meressa (Frontiers in Medicine)
Although pulmonary tuberculosis is a common infectious disease, especially in low-and middle-income countries, female genital tract tuberculosis (TB) is rarely reported. Female genital TB might be asymptomatic or manifest clinically in an unusual way, making an early diagnosis challenging. The most often affected regions of the genital system are the fallopian tubes and endometrium. Menstrual abnormalities, infertility, and chronic pelvic pain are frequent presenting symptoms. Rare reports of vulvar and vaginal TB exist. This case report features a 35-year-old woman who had a bulging tumor in her vagina for a year before being identified with anterior vaginal wall TB, treated with anti-tuberculosis medication, and made improvements.